2016
DOI: 10.1016/j.proghi.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A survey of clearing techniques for 3D imaging of tissues with special reference to connective tissue

Abstract: For 3-dimensional (3D) imaging of a tissue, 3 methodological steps are essential and their successful application depends on specific characteristics of the type of tissue. The steps are 1° clearing of the opaque tissue to render it transparent for microscopy, 2° fluorescence labeling of the tissues and 3° 3D imaging. In the past decades, new methodologies were introduced for the clearing steps with their specific advantages and disadvantages. Most clearing techniques have been applied to the central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 49 publications
3
146
0
2
Order By: Relevance
“…To determine differences in proliferation rates of GBM cells in MSC/GBM mixed xenografts, relative changes in fluorescence intensity of GBM cells between 1 day and 3 days after cell implantation were quantified using ImageJ (http://rsbweb.nih.gov/ij/; National Institutes of Health, USA). For confocal imaging, the embryos were fixed at 72 h after cell injection using 4% paraformaldehyde in phosphate-buffered saline for 2 h, and cleared in Sca l e U2, which was modified to enable visualization of carbocyanine-dye-labelled cells [60]. Imaging was performed with a TCS SPE confocal microscope (Leica) as described previously [34].…”
Section: Methodsmentioning
confidence: 99%
“…To determine differences in proliferation rates of GBM cells in MSC/GBM mixed xenografts, relative changes in fluorescence intensity of GBM cells between 1 day and 3 days after cell implantation were quantified using ImageJ (http://rsbweb.nih.gov/ij/; National Institutes of Health, USA). For confocal imaging, the embryos were fixed at 72 h after cell injection using 4% paraformaldehyde in phosphate-buffered saline for 2 h, and cleared in Sca l e U2, which was modified to enable visualization of carbocyanine-dye-labelled cells [60]. Imaging was performed with a TCS SPE confocal microscope (Leica) as described previously [34].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they showed that 3DISCO increased the signal to noise ratio while prolonging the integrity of the fluorescence. Furthermore, this protocol could be applied to a vast array of tissues ranging from lipid-rich structures such as the brain, but also extracellular matrix-rich structures such as gingiva [6]. Overall, 3DISCO offered a standardized protocol for clearing multiple tissues in a simple, efficient and cost-effective manner that was widely applicable.…”
Section: Clearing Strategiesmentioning
confidence: 99%
“…Tissue clearing protocols have since diversified into over 10 different clearing agents. The diversity of clearing protocols is beyond the scope of this article, for a comprehensive discussion on this topic you can refer to the following recent reviews [36]. What has become apparent in the past five years is that the field has split into two main approaches: i) solvent-based clearing, and ii) aqueous-based clearing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are many limitations, such as both limited and uneven penetration of the antibodies to the tissue sections, rendering full quantitative evaluation close to impossible. Now imagine there is no obstacle for antibodies to penetrate through the brain tissue and there is also no visibility limit (2), that is, we can see (using microscopy) through the brain (see the overview of clearing techniques [3]). Finally, let's assume that all the labor-intensive procedures in the scenarios are automated and, after few days of processing, the computers spit out quantified data registered per individual brain nuclei.…”
Section: Commentarymentioning
confidence: 99%